The influence of sports activities for personality of judoist - I.O. Beygul (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: the testing of personality quality, physical and psychical health of judoists within preparatory and contest periods of their activities. Material: 52 sportsmen, the age from 17 to 22 years old, have been took part in investigation. Results: found that the features of the influence of sports activities on the quality of individual athletes are caused by their stress tolerance and the conditions under which it is carried out (training or competitive). Significant and strongly influence the results of performances of athletes in competitions are such qualities as self-confidence, composure, calmness. Athletes are aware that they need to mobilize their strength and skills to be as active and ready for action in unfamiliar situations. Conclusions: the complication of activities conditions for sportsmen in contests period has been demonstrations presence of negative changes of personality virtue, absence of professional and qualitative psychological training.